Demographic, Histopathological and Clinical Features of Patients with Celiac Disease - Yusuf Kayar; Neslihan Sürmeli; Ramazan Dertli; Mehmet Ali Bilgili; Mehmet Ağın; Narin Yıldırım Doğan (Van Tıp Dergisi, 2019)
INTRODUCTION: Celiac disease (CD) is common in the world. In our study, we retrospectively evaluated the demographic, anthropometric, histopathological and clinical features of the patients followed up with the diagnosis of CD in our clinic. METHODS: Out of 23,250 patients admitted to our outpatient-clinic between 2009-2019, 250(1.07%) were diagnosed with CD. Total of 115 patients (18-65 years) were included in the study. Age, gender, onset of disease, duration of illness, family history, smoking, alcohol use, education, marital status, body mass index (BMI), waist-hip circumference and the symptoms of the patients at the time of admission were recorded. RESULTS: Of the patients, 85 (73.9%) were female and 30 (26.1%) were male. The mean age was 33+-10.6 years and the age of onset was 29.9+-5.8 years. The duration of the disease was between 0-17 years and the mean duration was 4.96+-3.6 years. Family history was seen in 26 (22.6%) patients. The number of smokers was 26(22.6%) and the number of patients using alcohol was one. Although the average BMI level is 22.1+-4.2; 20(17.3%) patients were weak. The waist-to-hip ratio of the patients ranged from 0.63-0.98, with an average of 0.81+-0.07. When the first presentation symptoms of the patients were evaluated; 83(72.2%) patients had symptoms related to gastrointestinal system (GIS), 22(19.1%) had non-GIS symptoms and 10(8.7%) had both GIS and non-GIS symptoms. DISCUSSION AND CONCLUSION: Although the classic findings such as grow thretardation and chronic diarrhea may be stimulating in celiac disease, they may present with atypical findings.